Study on The Development of Pioneering Routes at Bua Airport Based on Multi Creteria Analysis - Rauf, Irwan; Adisasmitha, Sakti Adjie; Hustim, Muralia (INTEK: Jurnal Penelitian, 2022)
This study aims to analyze the characteristics of the pioneering route from Bua Airport to other airports in South Sulawesi Province and to analyze the selection of priority pioneer routes from Bua Airport based on multi-criteria analysis. This research is non-experimental and much more based on descriptive qualitative and quantitative. Collecting data process is by using observation, documentation, and questionnaires. The respondents of this study were 100 respondents consisting of the public/passengers, employees and leaders of Bua airport. In this study, the AHP method is needed to make a decision whether to develop pioneer routes at Bua airport by opening several pioneer routes to other areas. The results of pairwise comparisons look at the characteristics of the selection criteria for pioneering route development criteria for distance 24.0%, travel time criteria 24.9%, cost criteria 25.8%, transportation mode criteria 13.6% and road network criteria 11.6%, therefore, the priority criterion in developing the pioneer route for Bua Airport is the cost criterion with a weight of 25.8%. The selection of priority pioneer routes for Bua Airport in comparison of alternatives with alternatives based on the criteria for the main area distance is Toraja 32.3%, the criteria for travel time to the main area of Toraja 38.6%, the criteria for the cost of the main area of Seko 32.8%, the criteria for the main mode of transportation Toraja 32, 5% and the main regional road network criteria are Toraja 31.9%, the priority pioneer route development for Bua Airport is Toraja 33.2%, the second area is Seko 29.2%, the third area is Rampi 19.2%, the fourth area is Masamba 9.8%, and the fifth area is Kendari 8.5%.